Pengaruh Pelatihan, Disiplin Kerja, dan Kompensasi Terhadap Kepuasan Kerja (Studi Pada Pegawai Kelurahan Sukabumi Selatan) - Saputra, Ilham; Hari Subagio (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The purpose of this study aims to investigate the effect of Training, Work Discipline, and Compensation on Job Satisfaction at the South Sukabumi Village Office. Using a Likert scale questionnaire, the study involved a sample of 62 respondents with the Non-Probability Sampling method and saturated sample technique. The results of multiple linear regression analysis in SPSS v.26 showed that Training had no effect while Work Discipline and Compensation had a significant effect on Job Satisfaction. These findings provide insight for management in managing Training as well as to improve supportive Work Discipline and Compensation conditions, with practical implications for improving employee/staff Job Satisfaction, organizational effectiveness, and recommendations for further research in this area.